AB0591 Nailfold Videocapillaroscopy May Not Reflect Change of Digital Ulcers Status in A Short Term Evaluation of Systemic Sclerosis Patients. (15th July 2016) - Bruni, C.; Ngcozana, T.; Braschi, F.; Barskova, T.; Guiducci, S.; Bellando-Randone, S.; Tofani, L.; Denton, C.P.; Furst, D.E.; Matucci-Cerinic, M.
Abstract : Background: Nailfold videocapillaroscopy (NVC) is a useful tool in systemic sclerosis (SSc) patients, useful not only for the diagnosis but also to predict the development of organ and vascular complications, such as the utility of the recently proposed semi-quantitative scoring for digital ulcers (DU) [1]. Objectives: to prospectively evaluate the change of prevalence of NVC microvascular alterations and their possible correlations with changes in patients-reported outcomes (PROs) and clinical-reported outcomes (CROs) and prevalence of clinical characteristics related to DU in SSc patients. Methods: SSc patients presenting at least one DU and attending the Rheumatology Wound Care Clinic of the Florence University Hospital or the London Royal Free Hospital were enrolled. Patients were assessed with PROs (HAQ-DI, UKFS, Cochin scale, VAS for pain, DU status and general disease status) and CROs (VAS for DU status) at baseline and after 16 weeks. DU number, appearance of new DU, presence of gangrene, infection, need for hospitalization or surgery procedures, painkillers use were recorded at each visit. NVC was performed at both visit and the presence of micro-haemorrhages, giant capillaries, irregularly enlarged capillaries, ramified capillaries, capillary disorganization and loss of capillaries was scored according to the previously proposed score (0 = no changes, 1 = from 0 to 33%; 2 = from 33% to 66%, 3 = more than 66%). Correlations were tested through Spearman test. Results: twenty-five SSc patients were eligible for the study. No significant correlation was seen at baseline; when analysing changes between baseline and follow-up, a negative correlation was seen between irregularly enlarged capillaries and the majority of PROs; moreover, changes of number of DU showed negative correlation with changes of giant capillaries, possibly reflecting the evolution of microvascular damage. Conclusions: NVC is useful tool to predicting DU development, but may not reflect short term change in DU status; therefore a longer-term evaluation may be necessary to detect NVC modifications paralleling DU changes in SSc patients. References: Smith V., Pizzorni C., De Keyser F, et al. "Validation of the qualitative and semiquantitative assessment of the scleroderma spectrum patterns by nailfold videocapillaroscopy: preliminary results, " Arthritis and Rheumatism, vol. 60, pp. S164–S165, 2009. Disclosure of Interest: None declared